A multi-sensor based fire fighting robot with wireless control and visual system - Hasan, Md. Mahmudul; Bhuiyan, Nayeem Al-Tamzid (Recent Research in Science and Technology, 2020)
Firefighting bot is a kind of robot by which we can detect the fire and extinguish it at the same time. In our project, we built a kind of robot that can automatically detect the location of the fire and can reach closer to the affected point and extinguish it as soon as possible. The extra advantage of our project is we built the robot both in autonomous and remote control mode. The remote control part is pretty much different from the other project because we used an android application to control the robot from the outside through the WIFI. The application is not directly connected with the robot. The robot and the application are both connected to the same server so that the application can give the command from anywhere from the word and the robot will get that command from the server through the WIFI system.